Variation in Species Composition, Size and Fitness of Two Multi-Species Sea Turtle Assemblages Using Different Neritic Habitats - Lamont, Margaret M.; Johnson, Darren (Frontiers in Marine Science, 2021)
The neritic environment is rich in resources and as such plays a crucial role as foraging habitat for multi-species marine assemblages, including sea turtles. However, this habitat also experiences a wide array of anthropogenic threats. To prioritize conservation funds, targeting areas that support multi-species assemblages is ideal. This is particularly important in the Gulf of Mexico where restoration actions are currently ongoing following the Deepwater Horizon oil spill. To better understand these areas in the Gulf of Mexico, we characterized two multi-species aggregations of sea turtles captured in different neritic habitats. We described species composition and size classes of turtles, and calculated body condition index for 642 individuals of three species captured from 2011-2019: 13.6% loggerheads (Caretta caretta), 44.9% Kemp’s ridleys (Lepidochelys kempii) and 41.4% green turtles (Chelonia mydas). Species composition differed between the two sites with more loggerheads captured in seagrass and a greater proportion of green turtles captured in sand bottom. Turtles in sand bottom were smaller and weighed less than those captured in seagrass. Although small and large turtles were captured at both sites, the proportions differed between sites. Body condition index of green turtles was lower in sand habitat than seagrass habitat; there was no difference for Kemp’s ridleys or loggerheads. In general, smaller green turtles had a higher body condition index than larger green turtles. We have identified another habitat type used by juvenile sea turtle species in the northern Gulf of Mexico. In addition, we highlight the importance of habitat selection by immature turtles recruiting from the oceanic to the neritic environment, particularly for green turtles.